Therapeutic effects of Qur’anic recitation (tilawah) on mental and physiological health: A PRISMA systematic review and meta-analysis with social solutions for community well-being - Pauline Hapsari; Darodjat (Islamic perspective on Communication and Psychology, 2026)
Background: The integration of Qur'anic recitation (tilawah) as a therapeutic intervention has gained increasing attention in recent years, with various studies suggesting its potential mental and physiological benefits. Despite promising evidence, the fragmented nature of existing studies has hindered a comprehensive understanding of tilawah's effects across diverse populations. This systematic review and meta-analysis aims to fill this gap by synthesizing empirical data on the therapeutic effects of Qur'anic recitation on both mental and physiological health. Methods: A systematic search was conducted across multiple databases, including Scopus, PubMed, and ScienceDirect, for studies published between 2000 and 2025. The review adhered to the PRISMA guidelines, and studies included were randomized controlled trials (RCTs), quasi-experimental studies, and pre-post intervention designs. Comprehensive Meta-Analysis (CMA) software was used to calculate effect sizes and assess heterogeneity across studies. Findings: A total of nine studies were included in the meta-analysis, assessing the effects of Qur'anic recitation on psychological outcomes like anxiety, depression, and stress, as well as physiological markers such as heart rate and cortisol levels. The meta-analysis revealed a small negative effect size (-0.309) with significant heterogeneity (I² = 92%), suggesting variability in the impact of tilawah across different studies and settings. Conclusion: Although the overall results did not reach statistical significance, individual studies indicated that Qur'anic recitation has therapeutic potential in reducing psychological distress and improving physiological health, particularly in Muslim-majority contexts. The study highlights the need for further research to standardize intervention protocols and explore factors like religiosity and cultural context that may influence the effectiveness of this intervention. Novelty/Originality of this article: This study offers a comprehensive synthesis of existing research on Qur'anic recitation, providing a valuable meta-analytic estimate of its therapeutic effects. It contributes new insights into the integration of spiritual practices into mental and physiological health interventions, with implications for culturally sensitive health strategies.